12 Feasibility of an online implementation toolkit for palliative care services seeking to implement a carer-centred process of assessment and support. Issue 3 (1st September 2018) - Diffin, Janet; Ewing, Gail; Rowland, Christine; Grande, Gunn
Abstract : Introduction: The Carer Support Needs Assessment Tool (CSNAT) intervention requires a change in practice to a carer-centred process of assessment and support. 1-3 An online toolkit was developed to guide palliative services through the process of implementing the CSNAT intervention. Aims: Explore the feasibility and acceptability of delivering implementation training through an online toolkit format. Methods: The online toolkit has two learning components: (1) Individual: knowledge for practitioners to use the intervention; (2) Organisational: to assist a project team to plan pilot and sustain implementation. Five UK palliative care services participated; 2–4 practitioners from each completed the toolkit. Online survey administered upon completion of each learning component for feedback on content followed by telephone interview. Results: 15 practitioners completed 'Learning component 1' survey 14 completed 'Learning component 2' survey and 13 were interviewed. Feedback on content was positive. Online learning suitability was influenced by resource availability the nature/size of the team and individual learning styles. Variation in location of completion (work/home or both) was partly explained by availability of IT equipment space and time within the organisation. Whilst the majority of participants saw the value of online learning some had a preference for face-to-face delivery and so blended learning to include group discussions was deemed appropriate. Conclusions: Whilst online learning is welcomed by practitioners organisations need to ensure sufficient resources are available to enable completion and that it is given the same priority as attendance at face-to-face workshops. Blended learning may help accommodate different learning preferences. Funder: NIHR CLARHC Greater Manchester References: . Ewing G, Grande G. Development of a Carer Support Needs Assessment Tool (CSNAT) for end-of-life care practice at home: A qualitative study. Palliative Medicine2013;27(3):244–56. . Ewing G, Brundle C, Payne S, Grande G. The Carer Support Needs Assessment Tool (CSNAT) for use in palliative and end-of-life care at home: A validation study. Journal of Pain and Symptom Management2013;46(3):395–405. . Ewing G, Austin L, Diffin J, Grande G. Developing a person-centred approach to carer assessment and support. British Journal of Community Nursing2015;20(12):580–4.